High-risk human papillomavirus testing as a primary screening for cervical cancer: position statement by the Korean Society of Obstetrics and Gynecology and the Korean Society of Gynecologic Oncology - Tae-Wook Kong; Miseon Kim; Young-Han Kim; Yong Beom Kim; Jayeon Kim; Jae-Weon Kim; Mi Hye Park; Joo Hyun Park; Jeong Ho Rhee; Myong Cheol Lim; Joon-Seok Hong (Korean Society of Obstetrics and Gynecology, 2020)
Based on emerging data and current knowledge regarding high-risk human papillomavirus (hrHPV) testing as a primary screening for cervical cancer, the Korean Society of Obstetrics and Gynecology and the Korean Society of Gynecologic Oncology support the following scientific facts:• Compared to cytology, hrHPV screening has higher sensitivity and detects more cases of high-grade cervical intraepithelial neoplasia.• Qualified hrHPV testing can be considered as an alternative primary screening for cervical cancer to the current cytology method.• The starting age of primary hrHPV screening should not be before 25 years because of possible overtreatment in this age, which has a high human papillomavirus (HPV) prevalence but rarely progresses to cancer. The screening interval should be no sooner than every 3 years and no longer than every 5 years.• Before the introduction of hrHPV screening in Korea, research into comparative effectiveness of primary hrHPV screening for cervical cancer should be conducted to determine the appropriate HPV assay, starting age, and screening interval.